E valuating inhaler use technique in COPD patients - Chaicharn Pothirat (2018)
© 2015, Pothirat et al. Background: Poor inhalation techniques are associated with decreased medication delivery and poor disease control in chronic obstructive pulmonary disease (COPD). The purpose of this study was to evaluate techniques for using inhaler devices in COPD patients. Methods: A prospective cross-sectional study was conducted to assess patient compliance with correct techniques for using inhaler devices across four regimens, ie, the pressurized metered-dose inhaler (pMDI), the pMDI with a spacer, the Accuhaler < sup > ® < /sup > , and the Handihaler < sup > ® < /sup > . The percentage of compliance with essential steps of correct device usage for each regimen was recorded without prior notification when COPD patients presented for a routine visit, and 1 month after receiving face-to-face training. We compared the percentage of compliance between the devices and risk factors related to incorrect techniques using logistic regression analysis. Percentage of patient compliance with correct techniques was compared between the two visits using the chi-square test. Statistical significance was set at P < 0.05. Results: A total of 103 COPD patients (mean age 71.2±9.2 years, males 64.1%, low education level 82.5%, and percent predicted forced expiratory volume in 1 second 51.9±22.5) were evaluated. Seventy-seven patients (74.8%) performed at least one step incorrectly. Patients using the Handihaler had the lowest compliance failure (42.5%), and the odds ratio for failure with the other devices compared with the Handihaler were 4.6 (95% confidence interval [CI] 1.8–11.8) for the pMDI, 3.1 (95% CI 1.2–8.2) for the pMDI with a spacer, and 2.4 (95% CI 1.1–5.2) for the Accuhaler. Low education level was the single most important factor related to incorrect technique (adjusted odds ratio 4.1, 95% CI 1.2–13.4, P=0.022). Formal training resulted in a statistically significant decrease in percentage of incorrect techniques for all devices and for the pMDI (59.4% vs 48.6%, P < 0.001; 72.4% vs 48.3%, P=0.039, respectively). Conclusion: Inhalation technique in COPD patients without face-to-face training was mostly unsatisfactory, especially in patients with low education levels. The Handihaler was the inhaler device associated with the lowest technique failure. Face-to-face inhalation technique training significantly increased technique compliance for the pMDI.